logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
Home  >>  CBSE XI  >>  Math  >>  Trigonometric Functions
0 votes

If $\sin(\theta+\alpha)=a$ and $\sin(\theta+\beta)=b$,then prove that $\cos 2(\alpha-\beta)-4ab\cos(\alpha-\beta)=1-2a^2-2b^2$

Can you answer this question?
 
 

1 Answer

+1 vote
Toolbox:
  • $\cos(a-b)=\cos a\cos b+\sin a\sin b$
  • $\cos 2\theta=2\cos^2\theta-1$
  • $\cos^2\theta=1-\sin^2\theta$
Given :
$\sin(\theta+\alpha)=a$
$\sin(\theta+\beta)=b$
$\cos2(\alpha-\beta)-4ab\cos(\alpha-\beta)=1-2a^2-2b^2$
Express $\cos(\alpha-\beta)=\cos[(\theta+\alpha)-(\theta+\beta)]$
$\Rightarrow \cos(\theta+\alpha).\cos(\theta+\beta)+\sin(\theta+\alpha).\sin(\theta+\beta)$
$\Rightarrow \cos(\theta+\alpha).\cos(\theta+\beta)+a.b$-----(1)
L.H.S
$\cos2(\alpha-\beta)-4ab\cos(\alpha-\beta)$
$2\cos^2(\alpha-\beta)-1-4ab\cos(\alpha-\beta)$
From (1) we have
$2[\cos(\theta+\alpha).\cos(\theta+\beta+ab]^2-1-4ab[\cos(\theta+\alpha).\cos(\theta+\beta)+ab]$
$2[\cos^2(\theta+\alpha).\cos^2(\theta+\beta)+a^2b^2+2ab\cos(\theta+\beta).\cos(\theta+\alpha)]-1-4ab\cos(\theta+\alpha).\cos(\theta+\beta)-4a^2b^2$
$2\cos^2(\theta+\alpha).\cos^2(\theta+\beta)+2a^2b^2+4ab\cos(\theta+\beta).\cos(\theta+\alpha)-1-4ab\cos(\theta+\alpha).\cos(\theta+\beta)-4a^2b^2$
$2[(1-\sin^2(\theta+\alpha)(1-\sin^2(\theta+\beta)]-1-2a^2b^2$
$2[(1-a^2)(1-b^2)-1-2a^2b^2$
$2[1-b^2-a^2+a^2b^2]-1-2a^2b^2$
$2-2b^2-2a^2+2a^2b^2-1-2a^2b^2$
$1-2a^2-2b^2$=R.H.S
Hence proved.
answered Apr 20, 2014 by sreemathi.v
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...